TRADISI LISAN PARIKAN DALAM DESAIN GRAFIS KAOS WISATA JAWA TIMUR - Jupriono, Jupriono (Universitas 17 Agustus 1945 Surabaya, 2016)
Tourism T-shirt with unique and funny words of textual graphic design are found in manycities in Indonesia, however which make use of parikan oral tradition have not been found, so it isnecessary to start bravely a parikan design tourism t-shirt production. Many sources of parikan canbe exploited, the parikan of ludruk artist creation as well as from campursari song creators, classicparikan and plesetan, also erotic parikan of individual creators, sounded in shows as well asrecorded in cassettes, CD, DVD, and internet. There are varied parikan which can be explored as thesubject of tourism t-shirt graphic design, and every type has its own market target according totypography consideration and communication norms. It needs requirements to sell tourism t-shirt:fulfilling market need, defining valuable product, offering unique subject, and entering market withthe precise name.Keywords: oral tradition, parikan, creative industry, typography graphic design, marketing strategy.